The role of digital public relations in promoting domestic tourism Saudi Airlines: Case Study for the year 2024 - Almutairi, Abdulla Hmood; Alheizan, Mohammed Abdulaziz (Journal of Humanities & Social Sciences, 2024)
This study aimed to identify the role of digital public relations in promoting domestic tourism in Saudi Airlines in the Kingdom of Saudi Arabia, by identifying the means, methods and fields used by digital public relations in Saudi Airlines to promote domestic tourism. To achieve the objectives of the study, the descriptive analytical approach was relied upon, and the interview was used as a tool for collecting data. The study community consisted of all employees of Saudi Airlines, while the study sample consisted of three managers of digital public relations in Saudi Airlines. The study reached several results; the most important of which are: that digital public relations in Saudi Airlines relies on advanced strategies to interact with the public through social media, websites, and applications, and focuses on building the brand. The study presented several recommendations; the most important of which are: the need for airlines to benefit from modern technology, such as artificial intelligence applications and its use to analyze customer data and provide personal recommendations for tourist destinations and offers.
Keywords: Public relations; digital public relations; Saudi Airlines; tourism promotion; domestic tourism